Effect of using different ratio of soil and coconut husk as a planting medium to the growth performance of oil palm seedlings / Mohamad Humaidi Harun - Harun, Mohamad Humaidi (Faculty of Plantation and Agrotechnology, 2015)
The aim of this research was to ascertain the influence of using soil and coconut husk as a planting medium on oil palm seedling growth. The research was conducted at green house and laboratory at University Teknologi Mara, Jasin Melaka from August 2014 until November 2014. This research was arranged in a Completely Randomized Design (CRD) with treatments. These treatments were (1) 100% coconut husk, (2) 100% soil, (3) 66% coconut husk + 33% soil, (4) 66% soil + 33% coconut husk, and (5) 50% coconut husk + 50% soil. The result showed that the medium of 66% soil + 33% coconut husk was the best medium for the growth of oil palm seedlings as it gave the highest for most parameters that being measured such as plant height, number of leaf, stem girth, and length of root except for the leaf area where the highest belong to treatment 100% soil.